Pengaruh Keyakinan dan Sikap Terhadap Keinginan Membeli Shampoo Dove di Yogyakarta - Widya Martina; Petra Surya Mega Wijaya (Fakultas Bisnis UKDW, 2006)
Promotion is an essential tool on determircireg the successfulness of marketing programme. The most importont component promotion is advertisment which has been widely used by many corporations to lauch a certain product.There are several media that can be used to advertise the product such as newspaper, radio, rnagazine, and television. By these influential means compony tries to form customer's belief and attitude toward their product which at least lead to the customer's intention to buy the productThe objective this study is to belief as well os the*ffict:of elti,fude ofl^eustemer:k*.et-erttiAn:'a,b*lt;:w*we**rbel,i€ft,.,wil!:be'repreaented:@,ths;adwrtisement fl&ssagaides-igni and wdor,&f gs wellAS;the bfAndiWQ€.The object,.oJ.#tis:':studvt.is,,lhe',ntagqawe'sr:glnwerciq!.;gfl, ,ofi:Dgpp,.Sho*npoo especiel'ly.;lhe, one tkot use l,rdon-egis!8,fqmaus;fl.tttistiiMqig';,4Mi:'T;l,w;:ornp.le, is drqyn purposively, resultd:rgfft;r&0? feWttrden#';iH,,Wgr&,e"",Structaral: Equati-an,,.klodelling (SEM, th€,:resultlpf,thtg;:itudX::*!,wusl'thattlke.,endorser and the design of Dove Shampoo's ad Estwell;.@":!l*W:brarldirnggetgf,Dove, Shampoo significantly affect the' custoW,er'q::Qllitgdet,,Morgever, theeff,ects ; of.. eustamerls. sttitude also demorusttca.le i,l,l,,:gntrte.gl ffi9t,,9v1,,customer's intention to buy.Keywords: advertisement, advertisement' :ico,,n, :, :qduprfiA,l Wgllt ,rf,ggiffir,advertisement' message, brand image;,:attitude; Cuslomc.r's r',igtf-sfitigrtr;,,554.,,Dove Shampoo",